The last word - Pellington, Mark, 1962-; MacLaine, Shirley, 1934-; Seyfried, Amanda; Sadoski, Thomas, 1976- (Universal City, CA : Universal Pictures Home Entertainment, 2017)
A successful, retired businesswoman decides to write her own obituary with the help of a young journalist.
Originally released as a motion picture in 2017.
Dolby digital 5.1, wide screen 2.40:1.
Shirley MacLaine, Amanda Seyfried, Thomas Sadoski, AnnJewel Lee Dixon, Philip Baker Hall.
MPAA rating: R.
Closed-captioned.
Keywords: Businesswomen -- Drama; Journalists -- Drama; Fiction films; Video recordings for the hearing impaired; Feature films; Comedy films